Comparison of water quality between sources and between selected villages in the Waterberg District of Limpopo Province; South Africa: with special reference to chemical and microbial quality. - Makgoka, Seretloane Japhtaline (My University, 2005)
Water and sanitation inadequacy is still an environmental health challenge in several regions worldwide and a billion people lack access to safe water, while 2.4 billion people have inadequate sanitation [2]. Assessment of water quality by its chemistry includes measures of elements and molecules dissolved or suspended in water. Commonly measured chemical parameters include arsenic, cadmium, calcium, chloride, fluoride, total hardness, nitrate, and potassium [16]. Water quality can also be assessed by the presence of waterborne microorganisms from human and animals’ faecal wastes. These wastes contain a wide range of bacteria, viruses and protozoa that may be washed into drinking water supplies [21]. Three villages were selected for water quality analysis, based on their critical situation regarding access to water and sanitation: namely, Matlou, Sekuruwe and Taolome villages, situated in the Mogalakwena Local Municipality within the Waterberg district of the Limpopo Province, South Africa. A proposal was written to the Province of North Holland (PNH) and was approved for funding to start with the implementation of those projects, with 20% of each village’s budget allocated for water quality research [26]. This was a cross sectional, analytical study to investigate the chemical and microbial quality of water in Matlou, Sekuruwe and Taolome villages. The study was also conducted to explore methods used by household members to store and handle water in storage tanks. Water samples were collected and analysed according to the standard operating procedures (SOPs) of the Polokwane Municipality Wastewater Purification Plant in Ladanna, Polokwane City of South Africa. The questionnaire used was adopted from the one used for cholera outbreak in the Eastern Cape Province of South Africa. Results show that water from all sources in all the villages had increased total hardness concentration. Water from the borehole in Matlou village had increased number of total coliform bacteria. There were increased total and faecal coliform bacteria in storage tanks samples from Matlou village. Water samples from reservoirs in Sekuruwe and Taolome villages did not test positive for any microbial contamination. Water from xiv informally connected yard taps in Sekuruwe village had increased total coliform bacteria, while increased total and faecal coliforms were found in households’ storage tanks. Water samples from communal taps in Taolome village had minimal number of total coliform bacteria, while water from storage tanks had both increased total and faecal coliform bacteria. Matlou village was the only place with increased nitrate concentration at the households’ storage tanks. While all the villages had microbial contamination, Taolome village had the least number of coliform bacteria in water samples from households’ storage tanks as compared to Matlou and Sekuruwe villages. It is concluded that water from sources supplied by the municipalities are safe to be consumed by humans while water from informally connected taps and households’ storage tanks are not safe to be used without treatment. It is recommended that a health and hygiene education package be prepared for all the villages, so that handling of water from the main source into their storage tanks can be improved. Secondly, it is recommended that water in all sources be treated for total hardness and water in storage tanks in Matlou village be treated for nitrate. Thirdly, it is recommended that water be accessed everyday of the week, so that people do not use unsafe water supplies.
Thesis (MPH)--University of Limpopo, 2005
Keywords: Water quality; Drinking water -- Contamination; Bacterial pollution of water; Ground water -- quality; Water -- Pollution -- South Africa; Water -- Storage